Kasus pembunuhan ferdy sambo terhadap brigadir yosua hutabarat - kinnayah ashifa; Rafel maita; Vasco Zacharias; Herli Antoni (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research discusses problems related to the criminal act of premeditated murder committed by the former head of the National Police Prompam Inspector General Pol. Ferdi Sambo, S.H., S.I.K., M.H against his own aide Brigadier Nofriansyah Joshua at the National Police's official residence. In this research there are two problem formulations including; 1) What is the regulation of the crime of premeditated murder committed by Ferdi Sambo? 2) what was the perpetrator's motive for carrying out the premeditated murder? This research is a normative legal research based on statutory regulations and data obtained by the author on social media. others can be subject to imprisonment for a maximum of twenty years and even the death penalty. The high-ranking police official who was named a suspect also threatened his subordinates who were members of the police not to report the premeditated murder and gave bribes to his subordinates in return for keeping their mouths shut